Targeting Cutaneous Leishmaniasis with Thiadiazine Thione Derivatives: An In Vivo Study of Its Anti-Inflammatory, Anti-Pyretic, Anti-Nociceptive, and Anti-Sedative Properties - Sarah Sarwar; Nadia Sarwar; Haleema Ali; Rafiullah; Rasool Khan; Ajaz Ahmad; Amin Ullah; Ho Soonmin; Nazif Ullah (Biomedicines)
Background/Objectives: Thiadiazine thione (THTT) has gained significant interest owing to its pharmacological potentials, particularly its antiparasitic and anti-inflammatory properties. Leishmaniasis is a clinical syndrome caused by infection with Leishmania species and is associated with an inflammatory response and nociception. The available treatments against leishmaniasis are inadequate, as they are associated with high cost, toxicity, and increased resistance. Methods: In the current study, the antileishmanial potential of five Thiadiazine thione derivatives (C1–C5) was evaluated in vivo against Leishmania tropica. Experiments were performed on BALB/c mice infected with promastigotes and treated with THTT derivatives for 15 days. Additionally, the derivatives were evaluated for their anti-inflammatory, antinociceptive, antipyretic, and antisedative properties using standardized models, including carrageenan-induced paw edema, acetic acid-induced abdominal writhes, yeast-induced fever, and white wood apparatus, respectively. Results: Of the tested derivatives, C5 exhibited the most promising results, with a 61.78% reduction in lesion size and significant decrease in parasite load. Among the derivatives, C1 showed the highest anti-inflammatory activity, with 63.66% inhibition in the paw edema test at the 5th hour post treatment. In the antipyretic assay, C1 and C5 were able to reduce body temperature to a normal level within 1 h of treatment. Furthermore, compounds C4, C2, and C1 showed high nociceptive activity, while C1 and C5 demonstrated the most notable antisedative effects (94 ± 2 and 92 ± 1, respectively), outperforming the standard drug diazepam (13 ± 1). Conclusion: These in vivo findings suggest that THTT derivatives have the potential to serve as a template for developing leishmanicidal drugs, with added anti-inflammatory and analgesic properties.